resolva essa equação (x-1)²+(x+2)²-9=0
Soluções para a tarefa
Respondido por
13
x²-2.x.1+1²+x²+2.x.2+2²-9
x²-2x+1+x²+4x+4-9
2x²+2x-4
x²+x-2
∆=1²-4.1.-2
∆=1+8
∆=9
x'=-1+3/2=1
x"=-1-3/2=-2
x²-2x+1+x²+4x+4-9
2x²+2x-4
x²+x-2
∆=1²-4.1.-2
∆=1+8
∆=9
x'=-1+3/2=1
x"=-1-3/2=-2
nathansouza12:
Obrigado!!
Respondido por
3
Resposta:
- 2 ; 1
Explicação passo-a-passo:
(x-1)²+(x+2)²-9=0
(x - 1) • (x - 1) + (x + 2) • (x + 2) - 9 = 0
x² - x - x + 1 + x² + 2x + 2x + 4 - 9 = 0
x² - 2x + 1 + x² + 4x - 5 = 0
2x² + 2x - 4 = 0
A= 2
B= 2
C= - 4
∆= 2² - 4 • 2 • ( - 4)
∆= 4 + 32
∆= 36
x= - 2 ± √36 / 2 • 2
x'= - 2 + 6/4 = 4/4 = 1
x''= - 2 - 6/4 = - 8/4 = - 2
S= ( - 2 ; 1)
Perguntas interessantes
Saúde,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Português,
1 ano atrás
Pedagogia,
1 ano atrás